Instant multigrain porridge: effect of cooking treatment on physicochemical and functional properties - Mandge, Harshad M. (Springer India, 2011)
Multigrain blends of wheat, mungbean, sorghum, barley, corn (50:20:15:10:5) and flaxseeds @ 1% were processed by instantization (cooking) treatments to produce instant multigrain porridge. Cooking treatment involved three processing steps, Soaking (A: Soaked for 5 h at 50 °C, B: Soaked for 3.5 h at 65 °C), Steaming at 15 psi for 10, 15, 20 min. and drying at 40 °C. Quality evaluation (physical, textural and sensory) of multigrain porridge was used as criteria to select the best processing condition for instantization. Per cent water absorption of grains increased significantly with increase in soaking time/temperature. Complete gelatinization of starch with no stickiness in cooked grains was obtained at 65 °C/3.5 h (soaking) followed by steaming (15 psi/15 min). The results suggest that multigrain blends can be instantized into an acceptable and nutritional, traditional breakfast food (porridge). The multigrain porridge given soaking treatment at 65 °C/3.5 h and steaming treatment for 20 min was having better physical and sensory properties.